Achieving COVID‐19 herd immunity in Bangladesh - Rabeya Mashferat Mary; Falguni Alam; Adriana Viola Miranda; Don Eliseo Lucero‐Prisno III; Md. Mofijul Islam Bulbul (Wiley, 2023)
Abstract Achieving herd immunity against COVID‐19 through vaccination is a global target, including in lower resource settings. Despite the challenges and limitations, Bangladesh has achieved its target of vaccinating 70% of its population, with good vaccine coverage among refugees, remote population, and women. This can be attributed to the evidence‐informed adaptability and collaborative approaches of the program. Yet some challenges remain, including dependence on donors and the need to ramp up vaccination among the underserved communities. This article discusses the factors contributing to the achievements of the COVID‐19 vaccination program of Bangladesh and the remaining challenges that should be addressed by the government to ensure the sustainability of the program and inform future vaccination efforts.